INTERVIEWING FOREIGNERS TO BROADEN STUDENTS’ UNDERSTANDING ACROSS CULTURE; A REFLECTION UPON A VIDEO PROJECT - Desri Sumbayak (Universitas Negeri Padang, 2013)
The group project to interview foreigners was given to students of Cross-Culture Understanding Class in English Department, FKIP, UR. After discussing the topic about cultural conflict and adjustment, as many 29 students were grouped into six. They were given time to design their questionnaire and to choose the foreigners who have been living in Pekanbaru for some times to be interviewed. They had two weeks to do the project. After finishing the project, they presented their video-recording of the interview in the class. Then, the students were asked to write reflection upon their project to see how it might help them to understand different culture. The result revealed that all the students thought that the project was significantly beneficial for them to understand the differences among cultures. They were also able to see the Indonesian culture from foreign people’s perspectives. Furthermore, most of students said that they learn how people make adjustments in a new culture. This experience taught them how to understand their own culture and to appreciate other culture.